Sunflower (Helianthus annuus L.) productivity under the effect of plant growth regulator in the conditions of insufficient moisture - Yerеmenko, Oksana; Еременко, Оксана Анатольевна; Єременко, Оксана Анатоліївна; Kalenska, S.; Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Rud, A.; Chynchyk, O.; Semenov, O. (TRAICON Publishing House, 2017)
It is shown that the use of plant growth regulators of antioxidant action for presowing treatment of oilseed crops can both oppress and stimulate germination processes. The plant growth regulator caused the activation of the growth process, which was particularly manifested through the height of plants and stem diameter. The increase in the leaf surface area of the crop by 39.3 % was defined by plant growth regulator and greatly depended on rainfall (r = 0.999) during the period of 00 65 on BBCH scale. Medium correlation (r = 0.588) was determined between rainfall in the phase of rapid growth and inflorescence diameter. Growth regulator affected the yield of sunflower significantly the share of a factor in the formation of yield was 32.7 %. The share of the impact of water deficit was 58.4 % on average over the years of research. Pollen fertility and seed emptiness of sunflower depended on relative humidity during flowering – r = 0.990 for the control plants and r = 0.973 in case of AKM application. The weight of 1000 seeds increased under PGR action by an average of 17 33 % depending on the zone of the inflorescence. In general, hybrids and plant growth regulator as researched factors significantly affect the yield of sunflower but the proportion of influence of hybrid (factor A) (85.1 %) is significantly higher than that of the impact of PGR (factor B) (7.5 %). This should be considered when developing anti-stress techniques in technologies of sunflower cultivation in the Steppe zone of Ukraine. Correlation of high strength was found between leaf surface area and rainfall (BBCH - 00-65) for all of hybrids (r = 0.868 – 0.996). AKM showed the greatest influence on the yield of sunflower plants of Zubr and Forvard hybrids, where fluctuation was within 14.3 - 31.3 %
Keywords: sunflower; productivity; plant growth regulator; hydrothermal conditions; growth and development of the plants; germination; stress resistance